2015
DOI: 10.3109/14397595.2015.1073133
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infection and delayed wound healing after orthopedic surgery in rheumatoid arthritis patients

Abstract: Our results indicated foot and ankle surgery, and TKA and disease duration as risk factors for SSI and DWH, respectively. bDMARDs was not associated with an increased risk of SSI and DWH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…As meta-analyses confirmed an increased risk of operative site infections of patients with diabetes mellitus (odds ratio [OR] 1.53), nicotine abuse (OR 1.79), and rheumatoid arthritis (OR 3.17), these risk factors were recorded in our study. 10,19,24…”
Section: Methodsmentioning
confidence: 99%
“…As meta-analyses confirmed an increased risk of operative site infections of patients with diabetes mellitus (odds ratio [OR] 1.53), nicotine abuse (OR 1.79), and rheumatoid arthritis (OR 3.17), these risk factors were recorded in our study. 10,19,24…”
Section: Methodsmentioning
confidence: 99%
“…However, patients in this trial were on a variety of medications, and multivariate analysis did find strong associations between steroids, penicillamine, cyclosporine, and hydroxychloroquine and adverse outcomes. Five observational studies 76 80 found no independent effect of immune-modulating therapy on wound or medical complications; however, these studies have methodologic limitations. None of these studies addressed the timing of discontinuation of agents nor did they address the ramifications of discontinuing therapy on rheumatoid symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Caution should be exercised not only during perioperative management but also for the development of late infection in rheumatoid patients being treated with biological agents. 36,37…”
Section: Discussionmentioning
confidence: 99%